KARAKTERISTIK PENDERITA KUSTA DENGAN KECACATAN DERAJAT 2 DI RS KUSTA ALVERNO SINGKAWANG TAHUN 2010-2013 - ., Aji Witama (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: Leprosy has been a health problem because of the grade 2disabilities. According to the data from Ministry of Health of Indonesia in2011, there were 2 052 cases of grade 2 leprosy in Indonesia. Objective:to describe the characteristics of leprosy patients with grade 2 disabilitiesat Alverno Leprosy Hospital Singkawang in 2010-2013. Method: It was adescriptive study with cross sectional approach. Result: There were 23samples and most of them were found to be at the age of 15-60 years old(100%), male (83%), graduated from primary school (48%), worked asfarmer/fisherman (75%), MB type (65%), had history of type 1 reaction(61%), had neuritis history (83%), had disability on feet (49%), complied tothe treatment (83%), the disability was found at the diagnosis (48%), andhad the symptoms for more than 1 year (91%). Conclusion: Most of theleprosy patients with grade 2 disabilities were found to be at the productiveage (15-60 years), male, worked as farmer/fisherman, graduated fromprimary school, MB type, had disability on feet, the disability was found atthe diagnosis, had history of type 1 reaction and neuritis, complied to thetreatment and had the symptoms for more than 1 year.Keyword: Leprosy, characteristics, second grade disabilities, Alverno LeprosyHospital